Exploring the Influence Mechanism of Brand Crisis on Consumer Repurchase Behavior - Zhang, Shuying (International Journal of Global Economics and Management, 2024)
The outbreak of a brand crisis can lead to an increase in public distrust of the brand, a sharp drop in sales, a blow to brand reputation and other phenomena, thus causing consumer dissatisfaction. How to repair the trust between brands and consumers, regain consumers' forgiveness and recognition can stimulate consumers repurchase behavior is a hot topic in society. Based on attribution theory, this study starts from the types of brand crises and explores the impact of brand crises on consumer repurchase behavior and the moderating role of brand awareness. On the basis of enriching the theoretical research on brand crisis management, this study also provides effective help for brands to formulate the perspective of crisis public relations program and rebuild brand image.